2020
DOI: 10.1016/s2468-1253(20)30014-5
|View full text |Cite
|
Sign up to set email alerts
|

British Society of Gastroenterology endorsed guidance for the management of immune checkpoint inhibitor-induced enterocolitis

Abstract: from voters who disagreed. Statements were only included if there was ≥80% agreement, otherwise there was an opportunity to review and modify the statement and enter into another round of electronic voting. If after two rounds there was continuing disagreement, if 50% of the group agreed and <20% disagreed, statements were accepted. The level of supporting evidence for each statement was assessed using the approach of the Oxford Centre for Evidence-Based Medicine 1 . This process took place over the course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 140 publications
(207 reference statements)
0
44
1
Order By: Relevance
“…7 11 Given that CPI-induced enterocolitis is the most common cause of CPI treatment interruption, permanent discontinuation and treatment-related death, 12 13 it is important to define optimal management strategies. Gastroenterology 14 and Oncology societal guidance 10 recommend institution of Open access corticosteroids as first-line anti-inflammatory therapy. In corticosteroid refractory disease, which occurs in over a third of patients, infliximab (IFX), an anti-tumor necrosis factor (TNF) monoclonal antibody, is recommended.…”
Section: Introductionmentioning
confidence: 99%
“…7 11 Given that CPI-induced enterocolitis is the most common cause of CPI treatment interruption, permanent discontinuation and treatment-related death, 12 13 it is important to define optimal management strategies. Gastroenterology 14 and Oncology societal guidance 10 recommend institution of Open access corticosteroids as first-line anti-inflammatory therapy. In corticosteroid refractory disease, which occurs in over a third of patients, infliximab (IFX), an anti-tumor necrosis factor (TNF) monoclonal antibody, is recommended.…”
Section: Introductionmentioning
confidence: 99%
“…Colonoscopy may still be useful in patients with treatment-refractory IMC as the presence of gross abnormalities in the proximal colon and persistent histologic evidence of IMC can inform the clinician's decision to initiate biologic therapy early in the treatment course. 7 Non-invasive biomarkers such as fecal calprotectin and lactoferrin have demonstrated utility in confirming the diagnosis of IMC [9][10][11] ; however, they are not routinely used to guide treatment. In addition, these biomarkers may not help identify alternative structural causes of gastrointestinal symptoms such as IMC with superimposed infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that CTCAE criteria for colitis and diarrhea alone may not accurately predict IMC severity and prognosis. 3,4 The role of endoscopy in diagnosing and assessing IMC severity has been studied 5,6 and, according to recent guidelines, 5,7 lower endoscopy with biopsy is considered the gold standard for diagnosing IMC in addition to ruling out alternative diagnoses. Nevertheless, the optimal lower endoscopic strategy (full colonoscopy or a limited flexible sigmoidoscopy) for obtaining biopsies and assessing severity of mucosal damage remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil accumulation in the colon is a key feature of CPI-colitis 27 , therefore, we also evaluated the colonic myeloid compartment. There was also signi cant accumulation of CD11b + Gr-1 high neutrophils and Ly6C high MHC class II − in ammatory monocytes in the colon of mice treated with FMT and CPI (Figs.…”
Section: The Composition Of the Intestinal Microbiota Regulates Susceptibility To Immune Checkpoint Inhibitor-induced Colitismentioning
confidence: 99%